A Comparative Analysis of the Electrochemical Performance Obtained for Magnetic Graphene Oxide-Based Composites - Escrig-Murua, J; Márquez-Mandiola, P; Márquez-Mandiola, P (ELSEVIER, 2021)
Low dimensional carbon allotropes are the most used materials in composites. In addition, when magnetic nanostructures are assembled with carbon-based materials, a versatile material for building sensitive electrodes is achieved. Here, we propose a route to obtain magnetic composites based on both graphene oxide and reduced graphene oxide with permalloy nanowires. A comparative analysis of the electrochemical performance for such composites reveals that a relatively small amount of magnetic nanowires leads to an increased conductivity with respect to that of the pristine matrix, being such effect more pronounced for the graphene oxide-based composite. Therefore, the presence of permalloy nanostructures plays a determinant role in the conductive properties of graphene oxide-based materials, providing an attractive alternative for sensing purposes. CO 2021 Elsevier B.V. All rights reserved.